Molecular mechanisms of rosmarinic acid from Salvia miltiorrhiza in acute lymphoblastic leukemia cells. (24th December 2015) - Wu, Ching-Fen; Hong, Chunlan; Klauck, Sabine M.; Lin, Yun-Lian; Efferth, Thomas
Abstract: Ethnopharmacological relevance: Rosmarinic acid (RA), a major hydrosoluble bioactive compound found in the Chinese medicinal herb, Salvia miltiorrhiza Bunge, which has been used in traditional Chinese medicine to treat various diseases, including cancer. However, the mechanisms have not been fully elucidated. Aim of the study: Guided by microarray hybridization and Ingenuity Pathway Analysis, we identified modes of action of rosmarinic acid (RA) isolated from S. miltiorrhiza on acute lymphoblastic leukemia cells. Materials and methods: Microarray data were verified by independent methods: Real-time RT-PCR (mRNA expression), resazurin assay (cytotoxicity of RA towards parental CCRF-CEM, multidrug-resistant CEM/ADR5000 cells and normal lymphocytes), flow cytometry (cell cycle arrest, apoptosis, necroptosis, generation of reactive oxygen species (ROS), disruption of mitochondrial membrane potential (MMP)), single cell gel electrophoresis (DNA damage), molecular docking and gene promoter binding motif analysis (NFκB), Western blotting (nuclear NFκB translocation, PARP cleavage, caspase 3/7/9 expression), and fibronectin-based cell adhesion assay. Results: RA dose-dependently inhibited CCRF-CEM and CEM/ADR5000 cells, but caused less cytotoxicity towards normal lymphocytes. RA simultaneously induced apoptosis and necrosis, as shown by cell morphology and annexin V-PI assay. DNA damage was dose-dependently induced without ROS generation, which subsequently led to cell cycle arrest. RA-stimulated MMP dysfunction activated PARP-cleavage and caspase-independent apoptosis. In accordance with molecular docking and gene promoter binding motif analyses, p65 translocation from the cytosol to the nucleus was blocked by RA, indicating a mechanistic role of the NFκB pathway to explain RA's action. RA affected cellular movement as evaluated by ameliorating cell adhesion to fibronectin. Conclusions: RA induced apoptosis and necrosis in a ROS-independent DNA damage and caspase-independent manner. These results may contribute to the rationale use of S. miltiorrhiza and RA in traditional medicine of leukemia. Graphical abstract: